Determinants of peripheral airway function in adults with and without asthma. Issue 6 (11th April 2017) - Robinson, Paul D.; King, Gregory G.; Sears, Malcolm R.; Hong, Chuen Y.; Hancox, Robert J.
Abstract: Background and objective: Peripheral airway involvement in asthma remains poorly understood. We investigated impulse oscillometry (IOS) measures of peripheral airway function in a population‐based birth cohort. Methods: Pre‐ and post‐bronchodilator spirometry and IOS measures of respiratory resistance and reactance were measured in 915 participants at age 38 years. Results: Current asthma was associated with impairments in both spirometry and IOS parameters. These impairments were greater in men and in those with childhood persistent asthma. Spirometry and IOS values for those whose asthma was in remission were not different to non‐asthmatic participants. There were significant changes in IOS in both asthmatic and non‐asthmatic participants after bronchodilator, but between‐group differences persisted. Higher BMIs were associated with impairments in IOS but not spirometry. Cumulative tobacco use was associated with spirometric airflow obstruction in both sexes, whereas cannabis use was associated with impairments in IOS in women. Despite higher lifetime exposure, there were few associations between cannabis and IOS in men. Conclusion: Asthma is associated with abnormalities in IOS measures of peripheral airway dysfunction. This association is stronger in men and in those with asthma persisting since childhood. Tobacco and cannabis use are associated with different patterns of spirometry and IOS abnormalities and may affect the bronchial tree at different airway generations with differences in susceptibility between sexes. Abstract : Peripheral airway function was impaired in adults with asthma and particularly those with childhood‐onset persistent asthma in a population‐based cohort of young adults. Higher BMIs were also associated with impaired peripheral airway function. Tobacco and cannabis had different effects on central and peripheral airways. See DOI: 10.1111/resp.13076